Exchange Rate Pass-Through in Turkey - Rossi, Marco (IMF Working Papers; Working Paper ;, 2002)
In light of the strong correlation between exchange rate movements and domestic prices in Turkey, it is important to assess the impact of the exchange rate on domestic prices, in particular as Turkey moves to an inflation targeting regime. This paper uses a recursive vector autoregression model to investigate the impact of exchange rate movements on prices in Turkey. We find that (i) the impact of the exchange rate on prices is over after about a year, but is mostly felt in the first four months, (ii) the pass-through to wholesale prices is more pronounced compared to the pass-through to consumer prices, and (iii) the estimated pass-through is complete in a shorter time and is larger than that estimated for other key emerging market countries.